PENERAPAN TEKNIK INVIGORASI DALAM MENINGKATKAN VIGOR BENIH PADI / Application of Invigoration Technique in Order to Improve Seed - Mira Landep Widiastuti; Sri Wahyuni (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
Seed is a component of production that contributes to increasing the national rice production. The use of low-quality seeds compared with production costs, non-uniform plant growth, yield reduction, and yield quality. One effort to improve the quality of seed vigor is through invigoration treatment. Invigoration technique among other hydration, thermal treatment, and coating. The hydration method is a water absorption system in seeds. Uncontrolled absorption (hydro-priming), by soaking and drying the seeds, hardening, on-farm priming, soaking for a certain period. The controlled system (osmo-priming) by immersing in osmotic solution, osmo-hardening (integration of hardening and osmo-priming), matri-priming with moist solid media, humidifications (with high humidity), and hormonal priming (with hormones. The second method is by temperature treatment, including by cooling and heating. The third technique is the coating treatment, namely coating the seeds. Hydration system hydro-priming for 30 hours can break seed dormancy with normal germination capacity of 91.3-99.3% in Memberamo, Cipunagara, and Maros varieties. The hardening technique is effective in increasing the germination of hybrid rice seeds for 12 hours with 2 cycles and for 24 hours with one cycle. The osmo-priming technique of soaking seeds in a 10 ppm GA3 solution or a mixture of 10 ppm GA3 + 15 ppm kinetin was effective in increasing the vigor of hybrid rice seeds. The matri-priming technique with rubbing ash as a medium plus the addition of 50 µ m GA3 was effective in breaking dormancy of the Membramo, Cipunagara, and Maros varieties of rice. It is can be applied, especially by small farmers.Keywords: Rice, seed, invigoration, quality AbstrakBenih merupakan komponen budi daya yang berkontribusi dalam meningkatkan produksi padi nasional. Penggunaan benih bermutu rendah berpengaruh terhadap penambahan biaya produksi, pertumbuhan tanaman tidak seragam, dan penurunan hasil dan mutu hasil. Salah satu upaya untuk meningkatkan mutu benih dari aspek vigor yang rendah adalah melalui perlakuan invigorasi. Teknik invigorasi dibagi menjadi tiga metode, yaitu hidrasi, perlakuan suhu, dan pelapisan (coating). Metode hidrasi merupakan sistem penyerapan air yang dapat terjadi pada benih. Penyerapan tidak terkontrol (hydro-priming) yaitu dengan merendam dan mengeringkan benih, pengerasan (hardening), on-farm priming yaitu merendam dalam jangka waktu tertentu. Sedangkan terkontrol (osmo-priming) dengan merendam pada larutan osmotik, osmo-hardening (integrasi hardening dan osmo-priming), matripriming dengan media padat lembab, humidifications (dengan kelembaban tinggi), dan hormonal priming (dengan hormon). Metode kedua adalah dengan perlakuan suhu, diantaranya dengan pendinginan dan pemanasan. Teknik ketiga adalah dengan perlakuan coating yaitu melapisi benih. Sistem hidrasi hydropriming selama 30 jam dapat mematahkan dormansi benih dengan daya kecambah normal 91,3-99,3% pada varietas Memberamo, Cipunagara, dan Maros. Teknik hardening efektif meningkatkan daya berkecambah benih padi hibrida selama 12 jam dengan dua siklus dan selama 24 jam dengan satu siklus. Teknik osmo-priming perendaman benih dalam larutan GA3 10 ppm atau larutan campuran GA3 10 ppm + kinetin 15 ppm efektif meningkatkan vigor benih padi hibrida. Teknik matri-priming dengan abu gosok sebagai media plus penambahan GA3 50 µm efektif mematahkan dormansi padi varietas Membramo, Cipunagara, dan Maros. Teknik invigorasi tersebut dapat diterapkan, khususnya oleh petani dengan skala produksi kecil.Kata kunci: Padi, benih, invigorasi, mutu